Thermal regime of the Northern Hikurangi margin, New Zealand. Issue 2 (30th October 2018) - Antriasian, Anson; Harris, Robert N; Tréhu, Anne M; Henrys, Stuart A; Phrampus, Benjamin J; Lauer, Rachel; Gorman, Andrew R; Pecher, Ingo A; Barker, Dan
Summary: We present 96 new seafloor heat flow determinations, made with a 3.5-m violin-bow probe and collocated with seismic reflection profiles, from the northern Hikurangi margin on the east coast of New Zealand's North Island. Here the Hikurangi Plateau on the Pacific Plate is subducting under the Australian Plate. The background heat flow is 58 ± 8 mW m −2, consistent with and within the variability of globally observed heat flow (56 ± 15 mW m −2 ) for oceanic crust 90–120 Ma, the age of the Hikurangi Plateau. Seaward of the deformation front, we find evidence for advective fluid flow associated with basement relief. Landward of the deformation front, we use a 2-D steady-state finite-element model to quantify the thermal regime. Despite corrections for the effects of bottom water temperature change, bathymetry and sedimentation, there is considerable scatter in the heat flow data including a local and sharp increase in heat flow of up to 35 mW m −2 observed over the outermost wedge. Variability in the heat flow data is likely due to complex, unmodelled 3-D fluid flow. We augment our heat flow measurements with estimates from a bottom-simulating reflection and continental bottom hole temperatures and conclude that the effective coefficient of friction, μ*, is approximately 0.06 in the region of observed slow-slip events and increases to 0.18 approximately 50 km landward of the deformation front. This transition in μ* may be marking the downdip edge of overpressures along the subduction thrust, suggesting that slow slip is enabled by overpressure.